2017
DOI: 10.1016/j.toxicon.2016.11.254
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR induced liver injury in mice and in primary human hepatocytes is caused by oncotic necrosis

Abstract: Microcystins are a group of toxins produced by freshwater cyanobacteria. Uptake of microcystin-leucine arginine (MC-LR) by organic anion transporting polypeptide 1B2 in hepatocytes results in inhibition of protein phosphatase 1A and 2A, and subsequent cell death. Studies performed in primary rat hepatocytes demonstrate prototypical apoptosis after MC-LR exposure; however, no study has directly tested whether apoptosis is critically involved in vivo in the mouse, or in human hepatocytes. MC-LR (120µg/kg) was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 49 publications
(67 reference statements)
2
15
0
Order By: Relevance
“…Some previous studies have confirmed hepatotoxicity, neurotoxicity, gastrointestinal toxicity, and reproductive toxicity of MC-LR [29][30][31][32]. However, the study of nephrotoxicity induced by prolonged oral exposure to MC-LR is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have confirmed hepatotoxicity, neurotoxicity, gastrointestinal toxicity, and reproductive toxicity of MC-LR [29][30][31][32]. However, the study of nephrotoxicity induced by prolonged oral exposure to MC-LR is rare.…”
Section: Discussionmentioning
confidence: 99%
“…MC-LR can accumulate in several tissues such as the liver, brain, ovary, intestine, kidney, and muscle [ 6 , 7 , 8 , 9 , 10 ]. The liver is the most affected organ in humans, followed by the gonads [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous literature [53], in the present study we selected the administration dose of DON of 1 and 3 mg/kg feed and fed piglets for 4 weeks. Herein, DON at 1 mg/kg elevated the ALT and GGT levels, suggesting that DON may destroy the liver cell membrane, leading toleakage of enzymes from injured hepatocytes [54,55]. However, compared with the 1 mg/kg DON group, DON at 3 mg/kg decreased serum levels of ALT, AST and LDH, especially AST and LDH, suggesting that 3 mg/kg DON may lead to massive necrosis of liver cells or acute hepatitis, basically resulting in depletion of transaminase in the liver tissue [56,57].…”
Section: Donmentioning
confidence: 99%